2008
DOI: 10.4049/jimmunol.180.11.7574
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a Synthetic TLR4 Agonist Protects Mice from Pneumonic Tularemia

Abstract: Francisella tularensis is a Gram-negative intracellular pathogen that causes the zoonosis tularemia. Because F. tularensis LPS causes weak TLR4 activation, we hypothesized that administration of a synthetic TLR4 agonist, aminoalkyl glucosaminide phosphate (AGP), would boost the innate immune system and compensate for reduced TLR4 stimulation. Intranasal administration of AGPs induced intrapulmonary production of proinflammatory cytokines and chemokines. Mice treated with AGPs before and after inhalation of Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 59 publications
4
51
0
1
Order By: Relevance
“…Poly(I:C) afforded protection against a mouse model of genital herpes simplex virus type 2 (17). Other investigators have demonstrated that TLR4 (24) or TLR9 (12, 13) agonist application increased cytokine production and prolonged survival in F. tularensis inhalation (24) or i.p. challenge mouse models (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(I:C) afforded protection against a mouse model of genital herpes simplex virus type 2 (17). Other investigators have demonstrated that TLR4 (24) or TLR9 (12, 13) agonist application increased cytokine production and prolonged survival in F. tularensis inhalation (24) or i.p. challenge mouse models (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Until such vaccines are available and widely distributed, alternate methods of broad range protection must be investigated. One interesting strategy is to engender innate immune resistance against mucosal pathogens (13,17,24). We have investigated the potential of Toll-like receptor (TLR) agonists recognized by TLRs highly expressed by respiratory epithelial cells.…”
mentioning
confidence: 99%
“…The rationale is to promote innate responses that greatly exceed in magnitude, quality, and dynamics the innate response triggered by the pathogen itself. The effectiveness of TLR agonists for therapeutic treatment of infectious diseases has been demonstrated in several animal models, including models of respiratory infections (6,21,35). TLR5 senses bacterial flagellins, which are the main constituents of flagella.…”
mentioning
confidence: 99%
“…However, in contrast to intranasal infection with an iglC-deficient mutant of F. novicida [8], inhalation of F. novicida ΔmglA does not confer protection against wild type pulmonary infection. We have demonstrated that protection against inhaled U112 infection in this system is feasible by the administration of intranasal TLR4 agonists [31]. We speculate that the lack of protective immunity induced by ΔmglA infection may be explained by the variable magnitude of IFN-γ production by sensitized splenocytes.…”
Section: Discussionmentioning
confidence: 96%